Code Switching Found in Photo and Video Captions Instagram of Angela Tanoesoedibjo - Damayanti, Ni Kadek Manik; Devi Maharani Santika, I Dewa Ayu (Humanis, 2024)
Humans possess the capacity to seek social engagement with individuals, employing not only a singular language but also several languages over the course of their life. The ability of mastering and using  more than one language has the effect of producing code switching. The aims of this study are to describe the types of code switching and language functions used by Angela Tanoeoedibjo's Instagram caption. Angela Tanoesoedibjo Instagram caption in 2021 which consist of code switching used as a data source in this study. The analysis is conducted using the descriptive qualitative method. This study used the theory from Poplack and Romaine (1995). Code switching consists of three types tag switching, intra-sentential switching, and inter-sentential switching. Additionally, Leech (1974) theories were used to analyze the language function of Angela Tanoesoedibjo Instagram caption. There has identified 6 tag switching, 16 inter-sentential switching, and 42 intra-sentential switching in this study. Furthermore, the five language functions are expressive, informative, directive, aesthetic, and phatic that found in this study